Preparation and Characterization of Interconnected, Kraft Lignin‐Based Carbon Fibrous Materials by Electrospinning. Issue 5 (15th October 2013) - Dallmeyer, Ian; Lin, Li Ting; Li, Yingjie; Ko, Frank; Kadla, John F.
<x xml:space="preserve">Abstract</x> Inter‐connected carbon sub‐µm fibrous materials are prepared by electrospinning of Kraft lignin solutions in DMF followed by thermal treatment consisting of oxidative thermostabilization at 250 °C and carbonization in the temperature range 600–1000 °C. Inter‐fiber bonding is achieved by taking advantages of the intrinsic differences in thermal mobility between different Kraft lignin fractions. Inter‐fiber bonding is observed to enhance the mechanical properties of both the thermostabilized and carbonized materials and enhances the electrical conductivity of the carbonized materials. The surface area, morphological, and structural characteristics are also characterized by the BET method, scanning electron microscopy, and Raman spectroscopy, respectively.<inline-graphic xlink:href="ark:/27927/pgg5nq98gb8" content-type="mame201300148-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />